Written monuments in old Prussian - Palmaitis, Letas (Knygotyra, 2024)
The appearance of historically testified written monuments in Old Prussian is connected with the beginning of the Christianization of Old Prussian tribes, i.e., with the aggression of the Catholic Teutonic Order against the Old Prussians and other peoples of the Baltic region in the 13th century.The oldest written monument in Old Prussian is the so-called “Elbing Vocabulary,” i.e., a German-Prussian glossary of 802 words found in 1825 by W. Neumann in Elbing. This manuscript was a copy from the end of the 14th century made by some P. Holzwescher from an older original, which may be dated to the beginning of the 14th century or even the end of the 13th century. Other known manuscripts in Old Prussian include a short glossary from the 16th century by S. Grunau, a number of samples of the Old Prussian speech registered by H. Maletius in Samland in the middle of the 16th century, a fragment of the “Pater Noster” from the 15th century, and an inscription in a folio of the 14th century found in 1974 by S. McCluskey in the library of the University of Basel (the so-called Basel epigram).Printed materials include only three items: two almost identical catechisms from 1545, containing 98 vs. 99 lines of Prussian text in different sub-dialects of Samland, and a translation of M. Luther's “Enchiridion” from 1561. The language of the latter catechism, i.e., the 3rd Prussian Catechism, is closer to that of one of the catechisms of 1545, named the 2nd Prussian Catechism, and deviates from the language of the other catechism of 1545, named the 1st Prussian Catechism. All three books were printed in Königsberg, the first two printed by H. Weinreich and the third printed by J. Daubmann.Although the catechisms were compiled in Samland, their phonetic features differ from those fixed in the Prussian toponymy of Samland, which conform to the phonetic features of all other monuments of Old Prussian: in all monuments except the Catechisms, as well as in the toponymy, there is the letter o corresponding to Lithuanian uo, Latvian uō, while there are the letters ū, o in these instances in the Catechisms. Since there were successors of 1600 Yatvingians deported after 1283 in Samland, a question arises whether the Catechisms really represent the Old Prussian and not the Yatvingian language.
Keywords: -